Geodetic Evidence of the Interannual Fluctuations and Long-Term Trends Over the Antarctic Ice Sheet Mass Change - Yuanjin Pan; Xiaohong Zhang; Jiashuang Jiao; Hao Ding; C. K. Shum (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The spatiotemporal characteristics of the Antarctic ice sheet (AIS), as constrained by geodetic observations, provide us with a deeper understanding of the current evolution of ice mass balance. However, it still needs further in-depth research on interannual fluctuations and long-term trends of ice mass changes throughout the AIS. In this study, these two aspects were quantitatively analyzed through global positioning system (GPS) and gravity recovery and climate experiment/follow on (GRACE/GFO) over the past two decades. The nonlinear variation of GPS-inferred vertical land motion (VLM) and the influence of surface elastic load are of particular concern. The principal component analysis method is utilized to extract common mode signals from GPS time series, while correcting for various surface loads. The first principal components (PCs) accounted for 57.67%, 35.87%, 36.28%, and 36.03% of the total variances in the vertical components for GPS raw, atmospheric + nontidal oceanic (AO)-removed, AO + hydrographic model (AOH)-removed, and AO + GRACE/GFO-based load (AOG)-removed, respectively. Furthermore, the GPS vertical velocity, excluding the common mode component + AOG, yielded a median value of 0.13 mm/yr, which indicates that the retreat of ice mass has made a significant contribution to the GPS-observed VLM. In addition, the glacial isostatic adjustment (GIA) effect is found to play a key role in the large-scale VLM uplifting of the West AIS. After evaluating five different GIA models with GPS vertical velocity, we suggest that the ICE-6G_D model can more effectively correct GIA signals in GPS observations over Antarctica.